Seasonal variation in high-risk phenotypes of cutaneous malignant melanoma diagnosed in Eastern England: An observational study. Issue 6 (June 2022) - Sharp, O.; Garioch, J.; Moncrieff, M.
Summary: Background: Despite seasonal variation in malignant melanoma diagnosis being well described, data on the annual variation in high-risk melanomas are scarce. Objectives: We set out to investigate the relationship between seasonality, the incidence of melanoma, and the distribution of melanoma characteristics, including Breslow thickness, ulceration, mitotic rate, lymphovascular and perineural invasion, and the presence of microsatellites. Methods: Primary cutaneous malignant melanomas diagnosed between 2011 and 2019 in Eastern England were identified from our prospectively maintained melanoma database ( n = 2199). These were analysed by year and season of diagnosis, patient demographics, and melanoma characteristics. Results: There was a variation in rates of melanoma diagnosis across the year, with Summer having the highest incidence ( p < 0.0001). There was a significant trend towards more male than female diagnosis in Winter ( p = 0.0354). There were no significant seasonal trends in Breslow thickness, ulceration, tumour infiltrating lymphocytes, or mitotic rate. Multivariate analysis showed that microsatellites were more likely to be diagnosed in the Winter (OR=2.00 (1.19–3.43), p = 0.010), lymphovascular invasion significantly more likely to be diagnosed in Autumn (OR=1.78 (1.16–2.76), p = 0.009), and perineural invasion was more likely to be diagnosed in the Summer (OR=0.44 (0.23–0.79), p = 0.007). Conclusions: These data confirm that high-risk phenotypes are associated with increasing Breslow thickness and mitotic rate. However, season variability as an independent risk factor for the phenotypes is a novel finding.